Visa and Immigration Trends: A Comparative Examination of International Student Mobility in Canada, Australia, the United Kingdom, and the United States. Issue 3 (October 2016) - Gopal, Anita
Abstract : This comparative study examines visa and immigration regulations for international students and focuses on macro‐level policy trends during the past five to ten years in four English‐speaking countries: Canada, Australia, the United Kingdom, and the United States. The study highlights the trends and motivations to recruit international graduate students as valuable skilled labor and potential designer immigrants in order to compete in the global economic market. Based on the analysis of policy documents and secondary data, it was found that there is a weak connection between higher education institutions and national security or customs and border protection agencies and the role that they play on international education. Also, the ease and expense of obtaining a student visa greatly influences international student enrollment trends.